A Study on the Pattern of Uveitis and Any Seasonal Variation in the Incidence of Uveitis at a Tertiary Care Hospital of Delhi, India - Hina Kauser; Farzana Islam; Taskin Khan; V.S. Gupta; Shivani Kochar (Delhi Journal of Ophthalmology)
Purpose: To analyze the patterns of uveitis and any seasonal variation in the incidence of uveitis at a tertiary care hospital of Delhi, India. Methods: The study included 100 new patients with uveitis examined in the Department of Ophthalmology at a tertiary care hospital of south Delhi, India from January 2016 to Dec 2017. We grouped the months of the year into winter, transitional and summer seasons according to the average temperature in New Delhi. Data was entered into Microsoft Excel spread sheet and analysis was done. Chi Square test was applied wherever necessary and p values were calculated at 95% confidence level. Results: There was male predominance (62%) with male to female ratio of 1.6: 1. The overall mean age of presentation was 35.4 years. The maximum number of patients were adults in the age group 31-40 years while the minimum were elderly above 60 years. Among all the cases, 44% cases occurred in the right eye, 40% in left eye and 16% had bilateral uveitis. Anterior uveitis was diagnosed in 88% of cases, posterior uveitis in 2%, and intermediate uveitis in 10% of cases. Out of 100 patients, 79% were idiopathic. A probable diagnosis was determined in 21% of cases; 10% cases were positive for HLAB27, and 5% were positive for tuberculosis. It was observed that there was seasonal trend in occurrence of the cases. Most of the cases occurred in the month of winter but no statistical significance was observed. (p value over seasons: 0.227603883; p transitional vs. winter season: 0.485499; p summer vs. winter season: 0.084838; p summer vs. transitional season: 0.3017). Conclusion: Idiopathic uveitis was highest in our study. HLA B27-associated uveitis was the most common noninfectious entity and tuberculosis was the leading cause for infectious entities in our study. Although the difference in the incidence of new acute uveitis among the three seasons was not statistically significant, a distinctly higher number of cases were seen in winters followed by transitional season and minimum in summers in both the consecutive years.